БОЛАЛАРНИ ЭРКАЛОВЧИ ХАЛҚ ҚЎШИҚЛАРИ - Шоймардонов, И. (SCIENCE and SOCIETY, 2020)
The article deals with importance of interpreting children’s Surkhan folk in upbringing spiritual-moral of children by means of childrens games and term which were recorded by Bakshi.
Keywords: folk songs; “lullabies”; “alla”; “huy-yo; huy-yo”; “hay yor-ey”; “long neck”; “licking sand”; “sanded”; “ashamed”; “Children chase camels”; “Huyya-bird”; “Let the one who catches a flower; let the iris be plentiful”; physical; moral; aesthetic; spiritual thinking